The Emergence of Artificial Intelligence in Higher Education: A Catalyst for Shifting the Status Quo - Cukierman, Uriel Rubén; Palmieri, Juan María (Springer, 2026)
The emergence of publicly available generative conversational artifi-cial intelligence (AI) tools such as ChatGPT, Gemini, and Copilot in late 2022, produced a major shift in modern society at every level. We may argue that the kind of effect was the same as with other technological advancements, but there are several very respected voices arguing that this is something completely dif-ferent. The educational environment is no exception to this shift. Considering this challenge, we started by the beginning of 2024 a new research project aiming to investigate the perceptions and concerns of engineering educators at the National Technological University (UTN) regarding the integration of AI tools in under-graduate courses. The overall goal of this research project is to identify the chal-lenges and opportunities presented by the emergence of AI in Higher Education, with a focus on Engineering Education, and how the institution and its members can adapt their practices to avoid inappropriate uses and adopt strategies that im-prove teaching and learning. Many organizations and groups have published nu-merous texts on aspects such as teaching, learning, assessment, and ethics. We selected 36 documents from various sources, including international organiza-tions, governmental agencies, and universities, and analyzed them to identify concurrent ideas and/or experiences that may support or challenge our previous suppositions and the results of the previous phase of this research project, which were presented in previous conferences.
Keywords: Artificial Intelligence, Engineering Education, Educational Innovation